Portrait photograph of an unidentified man (Boston, MA) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector::::::::::::; J. W. Black (photographer):::Photographer:::::::::::: (Boston, MA and Newport, RI; J. W. Black; United States, 2023)
Portrait photograph of an unidentified man (undated) from the studio of J. W. Black (Boston, MA and Newport, RI) from the personal collection of Alexander Wheelock Thayer.